Permissible dose : a history of radiation protection in the twentieth century - Walker, J. Samuel (University of California Press, 2000)
How much radiation is too much? This text examines the evolution, over 100 years, of radiation protection standards and efforts to ensure radiation safety for nuclear workers and the general public.